Helicobacter pylori vacA transcription is genetically-determined and stratifies the level of human gastric inflammation and atrophy - Sinnett, Charlotte G.; Letley, Darren P.; Narayana, Geetha L.; Patel, Sapna Rohitbhai; Hussein, Nawfal Rasheed; Zaitoun, Abed M.; Robinson, Karen; Atherton, John C. (BMJ Publishing Group Ltd, 2016)
Aims Helicobacter pylori infection is the major cause of peptic ulceration and gastric cancer, and an important virulence determinant is its vacuolating cytotoxin, vacA. Previously, we have described allelic variation in vacA which determines toxin activity and disease risk. We now aimed to quantify vacA mRNA expression in the human stomach, define its genetic determinants and assess how well it predicted gastric pathology. Methods Gastric biopsies were donated by 39 H. pylori-infected patients attending for endoscopy at Queen’s Medical Centre, Nottingham, UK. Total RNA was extracted, and vacA mRNA quantified by reverse transcriptase quantitative polymerase chain reaction. Separate biopsies were histologically scored for inflammation and atrophy using the updated Sydney system. H. pylori strains were isolated from further biopsies, and the nucleotide sequence upstream of vacA determined. Results vacA mRNA levels in human stomachs varied by two orders of magnitude independently of vacA allelic type. Among vacA i1-type (toxic) strains, increased vacA expression was strongly associated with higher grade gastric inflammation (p<0.02), neutrophil infiltration (p<0.005), and the presence of atrophy (p<0.01). A polymorphism at nucleotide +28 near the base of a potential stem- loop structure within the 5’ untranslated region was significantly associated with vacA transcript level and inflammation. Conclusions Increased gastric vacA expression during H. pylori infection is associated with inflammation and premalignant pathology. The +28 nucleotide within the vacA 5’ stem-loop stratifies disease risk amongst toxic vacA i1-type strains.